2011
DOI: 10.1021/jp2040967
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Excited States of Carotenoid Dyes Adsorbed on TiO2

Abstract: The fast development of new organic sensitizers for the purposes of dye-sensitized solar cells and photocatalysis requires a better understanding of the complexity of their electronic states on TiO2 surface. This paper describes a study of carboxylated derivatives of all-trans carotenoids retinoic acid (ATRA) and bixin by Stark effect (electroabsorption) spectroscopy in glassy ethanol at low temperature, both as free monomeric species and when adsorbed to nanoparticles of titanium dioxide in the presence of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 53 publications
0
8
0
1
Order By: Relevance
“…As seen in Fig. 2 The possible chemical reactions for the formation of ZnO nanoplate can be described as follows [8,9]; Zn(OH) are unstable intermediates and they are decomposed by microwave vibration by forming ZnO nuclei both (reaction 6) and (reaction8) [8,9]. We previously observed that the morphology of ZnO was changed by different KOH concentration.…”
Section: Zno Nanoplate and Fto-zno Photoanode Characterizationmentioning
confidence: 96%
See 1 more Smart Citation
“…As seen in Fig. 2 The possible chemical reactions for the formation of ZnO nanoplate can be described as follows [8,9]; Zn(OH) are unstable intermediates and they are decomposed by microwave vibration by forming ZnO nuclei both (reaction 6) and (reaction8) [8,9]. We previously observed that the morphology of ZnO was changed by different KOH concentration.…”
Section: Zno Nanoplate and Fto-zno Photoanode Characterizationmentioning
confidence: 96%
“…The sensitizers are the photo-harvesting materials such as ruthenium complexes, organic synthetic and natural dyes [2][3][4][5]. Several natural dyes have been employed as sensitizers in DSSCs, such as anthocyanin [6][7][8], carotene [9][10][11], chlorophyll [12,13] and tannin [14]. The plant-derived natural dyes are low cost and highly available alternatives.…”
Section: Introductionmentioning
confidence: 99%
“…Nanocząstki we wszystkich trzech przypadkach miały postać białego proszku, który wymagał mechanicznego rozdrobnienia i utarcia w moździerzu. Do nanocząstek dodawany był spotykany w opisach literaturowych α-terpineol [3] oraz kwas octowy, wybrany ze względu na wykazany we wcześniejszych badaniach udział w zapobieganiu agregacji nanocząstek oraz korzystny wpływ na przekaz ładunku elektrycznego w ogniwach DSSC [2]. Powstała po rozdrobnieniu masa była nakładana na szkło, a następ-nie wygrzewana w temperaturze 450 o C przez 45 min.…”
Section: Metodyka Badańunclassified
“…Several natural dyes have been employed as sensitisers in DSSCs, such as anthocyanin [16], chlorophyll [18], and carotene [19]. Pratiwi et al [20] used dragon fruit and red cabbage anthocyanin dyes as sensitisers for DSSCs, with conversion efficiencies of 0.024% and 0.054%, respectively.…”
Section: Introductionmentioning
confidence: 99%